2003
DOI: 10.1021/la026720w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of TiO2 Nanocrystals Prepared from n-Octadecylamine−Titanyl Oxalate Langmuir−Blodgett Films

Abstract: TiO2 nanosized clusters have been prepared by the Langmuir-Blodgett technique starting from the n-octadecylamine-titanyl oxalate complex. The floating film morphology has also been investigated by Brewster angle microscopy (BAM). The presence of TiO2 in the subphase promotes the formation of aggregates of n-octadecylamine on the subphase surface. LB films initially contain TiO2 nanosized clusters embedded in the organic amorphous matrix; their structural evolution induced by thermal annealing has been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…This indicates that a small percentage of gold nanoparticles do complex with the ODA monolayer under these conditions as well. At pH 12, the only possible interaction between the gold nanoparticle and the ODA monolayer would be hydrogen bonding and hydrophobic interaction [60]. It is clear that electrostatic interactions play a crucial role in the complexation process.…”
Section: Complexation Of the Gold Clusters With The Lipid Monolayermentioning
confidence: 99%
“…This indicates that a small percentage of gold nanoparticles do complex with the ODA monolayer under these conditions as well. At pH 12, the only possible interaction between the gold nanoparticle and the ODA monolayer would be hydrogen bonding and hydrophobic interaction [60]. It is clear that electrostatic interactions play a crucial role in the complexation process.…”
Section: Complexation Of the Gold Clusters With The Lipid Monolayermentioning
confidence: 99%
“…5b) in SCF-TiO 2 , which indicated that TiO 2 prepared via this method can make light at wavelengths of 320-350 nm completely transparent and is very useful when incorporated with polymer to produce selective transmission materials [39]. This phenomenon might be due to the particular pores and biological structures in the bamboo membrane, which interrupts the long-distance (Ti-OTi) n periodicity or TiO 2 crystal's disaggregation by the TiO 2 nanograin compensation as a result of mimicking of biological structures [40]. Further investigations on the mechanism of isolated Ti 4+ framework in tetrahedral coordination influenced by the biological mineralization will still need to be conducted [41].…”
Section: Resultsmentioning
confidence: 96%
“…The absorption peak located at 370 nm corresponds to the electronic transition from the valence band of oxygen (2p orbital of oxygen: O2p) to the conduction band of titanium [55]. This absorption band also reveals TiO 2 nanotubes (370 nm) compared to pure bulk anatase (373 nm) [56], while the absorption in the range from 400 to 500 nm is caused by the doping of TiO 2 thin films with Hg 2+ . We also note that the Hg 2+ -doped reflectance spectra show a slightly to longer wavelength with increasing the annealing temperature, associated with a dramatic decrease in the optical gap (3.51 to 3.10 eV) because the rutile phase has lower optical band gap compared to the anatase one.…”
Section: Reflectancementioning
confidence: 96%
“…The band gap reduction is favorable to the enhanced photocatalytic application of TiO 2 in the visible region. The bands around 544.12 nm are due to a green-yellow emission from the transition charge-carrier trapping of Hg 2+ -doped TiO 2 , while the yellow emission localized around 585.05 nm is associated with phonon emission in the yellow region from a recombination of free excitons [56]. The peaks centered around 612.06 nm and 637.37 nm can be attributed to red emission bands from the indirect transition of Hg 2+ -doped TiO 2 thin films.…”
Section: Reflectancementioning
confidence: 98%